Injury distribution analysis of the French handball championship using electronic game reports: a one-year longitudinal study among 323 628 players - Choupeaux, R.; Guegan, C.; Edouard, P.; Remy-Neris, O.; Picot, B. (British Journal of Sports Medicine, 2021)
Background Handball is one of the most traumatic Olympic sports, with a growing number of participants. Large sample size epidemiological studies across various playing levels are lacking in this sport.